Possible role of the 72,000 dalton DNA-binding protein in regulation of adenovirus type 5 early gene expression. - Carter, T H (1978)
Relative abundances of early virus RNA species in the cytoplasm of cells infected with wild-type adenovirus type 5 (WT Ad5) and a temperature-sensitive "early" mutant, H5ts125 (ts125), were compared by hybridization kinetics using separated strands of HindIII restriction endonuclease fragments of Ad5 DNA. 1-beta-D-Arabinofuranosylcytosine (ara-C) was used to limit transcription to early virus genes in cells infected by WT virus. At 40.5 degrees C, a restrictive temperature for ts125, three to seven times as much virus RNA from all four early regions of the genome accumulated in the cytoplasm of cells infected by the mutant as accumulated in cells infected by WT. At 32 degrees C, no such difference in the relative abundances of cytoplasmic virus RNA was observed. The capacity to synthesize a 72,000-dalton (72K) virus polypeptide, presumably the single-stranded DNA-binding protein that is defective in ts125 at restrictive temperatures, was compared in cells infected at 40.5 degrees C in the presence of ara-C with the mutant or WT Ad5. The rate of 72K polypeptide synthesis, measured by sodium dodecyl sulfate-polyacrylamide gradient gel electrophoresis of [35S]methionine-labeled polypeptides and autoradiography, was greater at 15 h after infection in ts125-infected cells than in cells infected by WT. A time course experiment showed that the rate of synthesis of the 72K polypeptide increased continuously in ts125-infected cells during the first 15 h of infection, relative to the rate in WT-infected cells. These data are consistent with the hypothesis that Ad5 early gene expression is modulated by the product of an early gene, the 72K DNA-binding protein.